If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -5)(5x + 1) = -5 Reorder the terms: (-5 + x)(5x + 1) = -5 Reorder the terms: (-5 + x)(1 + 5x) = -5 Multiply (-5 + x) * (1 + 5x) (-5(1 + 5x) + x(1 + 5x)) = -5 ((1 * -5 + 5x * -5) + x(1 + 5x)) = -5 ((-5 + -25x) + x(1 + 5x)) = -5 (-5 + -25x + (1 * x + 5x * x)) = -5 (-5 + -25x + (1x + 5x2)) = -5 Combine like terms: -25x + 1x = -24x (-5 + -24x + 5x2) = -5 Add '5' to each side of the equation. -5 + -24x + 5 + 5x2 = -5 + 5 Reorder the terms: -5 + 5 + -24x + 5x2 = -5 + 5 Combine like terms: -5 + 5 = 0 0 + -24x + 5x2 = -5 + 5 -24x + 5x2 = -5 + 5 Combine like terms: -5 + 5 = 0 -24x + 5x2 = 0 Solving -24x + 5x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-24 + 5x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-24 + 5x)' equal to zero and attempt to solve: Simplifying -24 + 5x = 0 Solving -24 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 5x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 5x = 0 + 24 5x = 0 + 24 Combine like terms: 0 + 24 = 24 5x = 24 Divide each side by '5'. x = 4.8 Simplifying x = 4.8Solution
x = {0, 4.8}
| 8a+5b+2b-5a= | | 66-7x=11x+18 | | x*2-5=3 | | 37-4*7= | | 8a+5b=2b-5a | | 2x+92=9x-13 | | x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a | | d=7h+12 | | 8*a^2+3a-800=0 | | 8*a^2+3a+800=0 | | 2x^3-6x^2+5x+6=0 | | -12h+30=-4h-17 | | 4x=5y+33 | | 15-(5-x)=1 | | 6(1-7k)=40-8k | | 3+2v=-6v+3 | | 2*log(x^2)+log(x-1)=0 |